Análise de Parafinas por APCI-FT-ICR MS : Uma Análise Rápida e Simples na Identificação de Hidrocarbonetos Saturados, Cíclicos e Poliaromáticos - Tose, Lilian Valadares (2014)
The analysis of hydrocarbon using atmospheric or ambient ionization techniques still remains a challenge in mass spectrometry. Traditionally, the ionization occurs via protonation or deprotonation. The molecules of interest must have a basic or acidic group to generated [M + H]+ or [M - H]- ions. To overcome such limitation, it is proposed a simple, easy, fast and powerful analytical methodology to ionize saturated (linear and branched), unsaturated, and cyclic hydrocarbons as well as polyaromatic and heteroaromatic hydrocarbonsby atmospheric pressure chemical ionization (APCI) using small hydrocarbons as reagents in a FT-ICR mass spectrometer. These molecules may be present in hydrocarbon fraction samples and paraffin/crude oil blends. Among the APCI hydrocarbon reagents studied, isooctane provided the best results when compared to pentane, hexane, cyclohexane and heptane. The method renders the ionization of hydrocarbons to yield [M – H]+ ions with no associated fragmentation using nitrogen as sheath gas.